Perceived role of the veterinarian in promoting dairy cattle welfare - Brunt, Michael W.; Haley, Derek B.; LeBlanc, Stephen J.; Kelton, David F. (Frontiers in Veterinary Science, 2023)
Improving the lives of animals in agricultural systems has primarily focused on minimizing negative experiences. Research is needed on the promotion of positive experiences (pleasure, enjoyment, play, choice, happiness) for animals and the role of veterinarians in their promotion. Our aims were to describe how Canadian bovine veterinarians and veterinary students perceive the role of a veterinarian in positive vs. negative experiences for dairy cows and to analyze the rationale provided to explain their answers. Canadian veterinary practitioners (n = 78) and veterinary students (n = 148) responded to an online cross-sectional survey and were asked, on a 7-point scale, how important the role of a veterinarian is to promote practices that influence the experience of dairy cows. We used qualitative description to analyse participants' open-ended text responses. Practices to minimize negative experiences were most important (mean ± SE; 6.8 ± 0.03), a balance of positive and negative experiences was less important (6.4 ± 0.05), and encouragement of positive experiences scored lowest (6.0 ± 0.06), although all scored highly. Four themes were identified to explain participants' reasoning regarding their perceived role of a veterinarian in the promotion of dairy cattle welfare, centered on: the animal, the producer, the veterinarian, and society. Participants indicated that promoting positive experiences was less important than decreasing negative experiences (5.9 ± 0.09). There were four themes identified to explain participants' reasoning regarding the relative importance of promotion of positive experiences versus decreasing negative experiences which centered on: frameworks to compare positive and negative experiences, impacts on the animal, the participant's view of their role, and the practicality of implementation. These results indicate modest differences in valuing avoidance of negative vs. promotion of positive welfare. There were no differences in the quantitative analyses between veterinarians and veterinary students. We conclude that veterinarians are favourably disposed to positive aspects of welfare for dairy cows but may be more focussed on avoidance of negative aspects of welfare.